Banks as Secret Keepers - Dang, Tri Vi; Gorton, Gary; Holmström, Bengt; Ordoñez, Guillermo (American Economic Review, 2017)
Banks produce short-term debt for transactions and storing value. The value of this debt must not vary over time so agents can easily trade it at par like money. To produce money-like safe liquidity, banks keep detailed information about their loans secret, reducing liquidity if needed to prevent agents from producing costly private information about the banks' loans. Capital markets involve information revelation, so they produce risky liquidity. The trade-off between less safe liquidity and more risky liquidity determines which firms choose to fund projects through banks and which ones through capital markets. (JEL D92, E51, G21, G31, G32)